1986
DOI: 10.1002/jcp.1041270208
|View full text |Cite
|
Sign up to set email alerts
|

Forskolin, phosphodiesterase inhibitors, and cyclic AMP analogs inhibit proliferation of cultured bovine aortic endothelial cells

Abstract: The role of cyclic AMP on endothelial cell proliferation was investigated, since these cells can be exposed to high concentrations of physiological and pharmacological agents that alter cyclic AMP metabolism. Cloned bovine aortic endothelial cells were plated at 25,000 cells/35mm dish and grown for 5 days in the presence of phosphodiesterase (PDE) inhibitors, forskolin, or cyclic AMP analogs. The PDE inhibitors dipyridamole, ZK 62 711, isobutylmethylxanthine (IBMX) and theophylline inhibited cell growth in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 42 publications
4
26
0
1
Order By: Relevance
“…The long-term effect of PDE2 and PDE4 inhibition in the cobblestone phenotype suggests that the increase in cAMP due to PDE inhibition contributes to maintaining the cobblestone phenotype, and to preventing the appearance of proliferating cell types which is required for angiogenesis. This is in agreement with the antiproliferative effect reported for cAMP in endothelial cells [9]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The long-term effect of PDE2 and PDE4 inhibition in the cobblestone phenotype suggests that the increase in cAMP due to PDE inhibition contributes to maintaining the cobblestone phenotype, and to preventing the appearance of proliferating cell types which is required for angiogenesis. This is in agreement with the antiproliferative effect reported for cAMP in endothelial cells [9]. …”
Section: Discussionsupporting
confidence: 82%
“…A cross-talk between PDEs mediated by cGMP may participate in intracellular signalling [1, 7, 8], and furthermore, cyclic nucleotides have been shown to be important endogeneous regulators of cell proliferation. Endothelial cell growth inhibition is associated with an elevation of intracellular cAMP [9], while either a decrease [10]or an increase [11]in intracellular cGMP has been reported to inhibit growth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fibronectin was shown to stimulate Schwann cell growth ' isobutylmethylxanthine (IBMX) is partially active in enhancing the cellular response to FGFs. Elevated intracellular cAMP levels by forskolin or phosphodiesterase inhibitor treatment were shown to be growth inhibitory in bovine aortic endothelial cells (Leitman et al, 1986) and human foreskin fibroblasts (Heldin et al, 1989). In this report, we showed that the growth response of fibroblasts isolated from connective tissues surrounding the sciatic nerves to bFGF was also slightly inhibited by forskolin at a concentration that was optimally stimulatory for Schwann cells.…”
Section: Discussionmentioning
confidence: 76%
“…cAMP has been shown to enhance or inhib it cell proliferation depending on the cell type used. Inhi bition of proliferation was observed with bovine aortic EC [31], pig aortic EC [32], and rat brain microvascular EC [33], whereas stimulation was observed in a fetal bovine aortic EC line [34], Furthermore, cAMP levels are increased by a number of growth factors [14] and eleva tion of cAMP can lead to reversal of the transformed phe notype [15]. The antitumor activity of the cAMP analog 8-Cl-cAMP may be due to its ability to restore normal gene transcription in tumor cells through an action on type II PKA [10].…”
Section: Discussionmentioning
confidence: 99%